RELEVANSI HUKUM KEEMPAT TEORI RANGANATHAN DALAM PERKEMBANGAN LAYANAN PERPUSTAKAAN DI ERA SOCIETY 5.0 - Khairiyah, Mishbahul; Labibah Zain (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Humaniora Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
SR Ranganathan was one someone who significantly improved the subject about library science, whose five laws of libraries state: 1. Book are meant to be use, 2. Readers are books, 3. Readers are books, 4. Saves time for the reader and, 5. Libraries are living things. In other word, the research employed a desciprive qualitative approach, data analysis follows the Milles Huberman model,which entails gathering refinig, presenting, and ultimately drawing conclusion from the data. This study is related to the fourth law and the “Society 5.0 era”, which includes the usage of RFID Technology, continously digital service, and OPAC (Online Public Access Catalog) for the collection tracking. The fourth law of Ranganathan’s theory, according to the conclusion, positively affect librarie development and maintains up with modern times